Supporting early child bilingualism : the role of parents with limited English proficiency / Nur Afifah binti Addenan - Addenan, Nur Afifah (2014)
Bilingualism is becoming a growing trend in Malaysia due to the role of the English language in this technological era and a necessity for today’s development. Bilingualism involving proficiency in English and any one of the local languages is now widely considered as an asset for socioeconomic mobility in Malaysia. The desire to be successful, both socially and economically nowadays is starting to force Malays into becoming Malay-English bilinguals. The position of English has influenced even parents with Limited English Proficiency (LEP) in Malaysia into striving to embed the knowledge of both their native language and English in their children at an early age. This research investigates the support strategies used by 25 parents with LEP in achieving their goal. This study focuses only on Malay parents with limited English proficiency who are currently raising their children into becoming bilingual regardless of their own deficiency in the knowledge of English. This research reveals the potential motivational ifactors that influence iparents to isupport early child bilingualism and identifies the appropriate strategies of support adopted in achieving their goal to iraise iMalay/English-bilingual children.